Ekoteologi dalam Bingkai Pluralisme: Landasan Teologis Kolaborasi Lintas Agama untuk Menghadapi Krisis Iklim - Gando Iman; Almahmudi Imami; Sultan Jayakusuma; Rahman Fithra; Sutarman Jayadi (Yayasan Albahriah Jamiah Indonesia, 2025)
The global climate crisis, which increasingly threatens the sustainability of life, demands a collaborative approach that transcends religious traditions. Meanwhile, interfaith ecotheological studies that systematically link theological pluralism with ecological ethics remain limited, thereby creating an academic need to formulate a common theological foundation. This study aims to identify, compare, and synthesise the principles of ecological ethics from Islamic, Christian, Hindu, and Buddhist traditions, thereby building a model of ecotheological collaboration as a conceptual framework for interfaith dialogue and action. Using a qualitative theological-comparative method, the study analyzes canonical texts and interfaith documents through a hermeneutical approach, establishing source selection criteria based on doctrinal authority, ecological relevance, and traditional representation. The results indicate three groups of universal principles: first, the concept of cosmic responsibility—Islam emphasizes amanah, Christianity emphasizes stewardship, Hinduism views nature as part of ṛta, and Buddhism emphasizes the interconnectedness of life (pratītyasamutpāda); second, the ethics of moderation and self-control as a pattern of ecological life; and third, environmental justice as a collective spiritual obligation. This synthesis yields a collaborative ecotheological model encompassing four dimensions: a shared theological basis, a space for intertraditional dialogue, practical ecological ethical guidance, and an action orientation for environmental justice advocacy. Theoretically, this research strengthens pluralistic theological discourse by offering interfaith ecological meeting points, while practically, it provides an ethical framework applicable to collaborative programs for planetary sustainability.